The mediating role of primary sclerosing cholangitis in the association between ulcerative colitis and hepatobiliary cancer investigated through Mendelian randomization - Wang, Fangming; Xiao, Junhui (Scientific reports, 2024)
This study explored the causal relationships among primary sclerosing cholangitis (PSC), ulcerative colitis (UC), and hepatobiliary cancer (HBC) by using bidirectional two-sample, two-step Mendelian randomization (MR) analysis. Genetic variants associated with PSC and UC from the FinnGen research database were used for instrumental variable-based analyses. Mediation analyses were conducted to examine the role of PSC and UC in HBC risk. The findings revealed a causal effect of genetic predisposition to UC on PSC risk (inverse-variance-weighted [IVW] analysis odds ratio [OR] 1.145, p < 0.001), whereas no reverse causality was observed. Although UC showed no direct causal effect on HBC risk, genetic susceptibility to PSC significantly increased the risk of HBC (IVW analysis OR = 1.855, p < 0.001). Mediation analysis further identified PSC as a significant mediator amplifying the causal effect of UC on HBC risk (effect size = 0.083). These results established a causal link between genetic susceptibility to UC and increased risk of PSC, and highlighted the critical role of PSC in mediating the impact of UC on HBC risk.